Flexible Cystoscopy a Valuable Diagnostic Lool for Lower Urinary Tract Pathology (Bangladesh Journal of Urology, 2020)
Objective: To assess the role of flexible cystoscopy in the diagnosis of lower urinary tract pathology and its suitability as a routine diagnostic protocol in outdoor patients.Methods: The cross sectional study was conducted at the advanced centre of kidney diseases and urology, Dhaka central international medical college, Dhaka from Jan 2016 to jan2019. All adult patients presenting with lower urinary symptoms to outdoor department were included. Flexible Cystoscopy was performed as a outdoor based procedure without sedation.Results: Of the 249 patients in the study,198(79%) were male and 51(21%) were female. Lower urinary tract pathologies were found in 192(72%) patients. The most common pathology among males was enlarged prostate 56(31%) patients. Urethral stricture, bladder neck high were found 23(11%),21(10%) respectively. Among females, urethral stenosis was the most common pathology in 23(32%)patients. Transitional cell carcinoma was seen in 11(4.4%) patients having hematuria with inconclusive ultrasound and intravenous urography. .All patients tolerated the procedure well with no procedure related complaints.Conclusion: Flexible cystoscopy is an effective, well tolerated and easy way of detecting lower urinary tract pathologies. It can alter the management as well as support the diagnosis and management. It is also helpful in routine surveillance of bladder tumours of low grade and low stage. Flexible cystoscopy should therefore be used as routine diagnostic protocol in outdoor practice.Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.151-153